Balancing market needs and education objectives (The case of higher education transformation) - Al-Allak B.A.; Saeed M.A.; Alnaser A.S. (2023)
Today, the orientation toward success in life is becoming one of the leading life strategies of college students at higher educational institutions, and of young people in general, under current market conditions. Starting from "Deweyan perspective, educational transformation must be seen as strictly connected to social change, and education should be understood as a process that facilitates and supports social growth and development." This paper aims to: - Discuss connections between teaching and learning processes. - Discuss connections between transformation and learning. - Discuss Peters' critical perspective on teaching as it relates to the learner's transformation through education. - Examine connections between transformations and learning within classical and contemporary education philosophical discourse. On the other hand the current paper will also highlight: - The role of the economic factor in the choice of a future profession. - The motives for enrolling in an institution of higher learning. Finally, conclusions and some recommendations for development of education will be presented.